Comparative Efficacy of PAG-based Rapid Strip Test Kit, Ultrasonography and Per Rectal Palpation for Early Pregnancy Diagnosis in Cattle and Buffaloes - J. Devmurari, Yash; B. Vala, Karsan; S. Parikh, Suryakant; P. Vijyeta, Hardeep; J. Dhami, Arjan; Z. Solanki, Jayesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to evaluate and compare the accuracy and reliability of different methods of pregnancy diagnosis like PAG-based BovEasy rapid PD strip test kit at days 28, 32, 36 and transrectal ultrasonography on day 28 against per rectal palpation on day 45 post-AI for detection of early pregnancy in Gir cows and Jaffarabadi buffaloes. 22-days non-return postpartum healthy animals comprising 75 Gir cows and 75 Jaffarabadi buffaloes, (150,) aged 4 to 14 years, were selected from the Cattle Breeding Farm, KU, Junagadh. The BovEasy bovine rapid pregnancy detection test kits on Days 28, 32, and 36 post-AI showed high accuracy, sensitivity, and specificity across all time points in detecting early pregnancy as confirmed by USG on day 28 and per rectal palpation on day 45. For Gir cows, accuracy increased from 97.33% (on day 28) to 100% (on days 32 and 36), while Jaffarabadi buffaloes demonstrated 100% accuracy across all days. The combined data of cattle and buffaloes revealed accuracy improvement from 98.67% (on day 28) to 100% (on days 32 and 36), with sensitivity and specificity reaching 100%. The accuracy of transrectal ultrasonography on Day 28 post-AI for pregnancy was verified by presence of amniotic vesicle and fetal heartbeats against strip test on day 28 and per rectal palpation on day 45. It demonstrated 100% accuracy, sensitivity, and specificity in both breeds, with no false positive or negative result. The overall actual pregnancy rate was 36.7% (55/150). Overall, embryonic mortality was 4.7% (7/150). Reliability of early pregnancy detection methods when validated against per-rectal palpation results on Day 45 post-AI showed the similar results in both the species. Conception rate with diagnostic methods and embryonic mortality though higher in Gir cows did not differ from those in Jaffarabadi buffaloes.